Non-uniform Intelligent Down-sampling of Digital Curves for Efficient Compression - N Shylashree; Sachin Kumar (Brazilian Archives of Biology and Technology)
Abstract A new method is proposed for the intelligent down-sampling of digital curves that provides efficient compression. The proposed down-sampling is non-uniform and is based on the spatial distribution of points on the digital curve (line diagram). The down-sampled points form a polyline or polygon which is an approximate representation of the input digital curve. The down-sampled points are determined using an optimization solver, such that the differential area between the original digital curve and the optimally generated down-sampled polyline or polygon, is minimal. The mean percentage execution time saved by our proposed method, compared to its nearest competitor, is found to be about 18%.